Nanotechnology against human cytomegalovirus in vitro: polyanionic carbosilane dendrimers as antiviral agents - I. Relaño-Rodríguez; M. S. Espinar-Buitrago; V. Martín-Cañadilla; R. Gómez-Ramirez; J. L. Jiménez; M. A. Muñoz-Fernández (Journal of Nanobiotechnology, 2021)
Abstract Background Human cytomegalovirus (HCMV) is a worldwide infection, causing different troublesome in immunosupressed patients and very related to Human Immunodeficiency Virus 1 (HIV-1) infection, mainly in developing countries, with a co-infection rate of 80% in Africa. The high cost of present treatments and the lack of routinely tests in these countries urge the necessity to develop new molecules or strategies against HCMV. The new treatments should be low-cost and capable of avoiding the emerging problem of resistant virus. Nanoparticles play an important role in several viral infections. Our main focus is to study the potential activity of polyanionic carbosilane dendrimers (PDC), which are hyperbranched molecules with several sulfonate or sulfate groups in their periphery, against different viruses. Results We studied the activity of G1-S4, G2-S16 and G2-S24P PDCs in MRC-5 cell line against HCMV infection by several plaque reduction assays. Our results show that dendrimers present good biocompatibility at the concentrations tested (1–50 µM) for 6 days in cell culture. Interestingly, both G2-S16 and G2-S24P showed a remarked inhibition at 10 µM against HCMV infection. Results on attachment and virucidal assays indicated that the inhibition was not directed to the virus or the virus-cell attachment. However, results of time of addition, showed a longer lasting activity of these dendrimers in comparison to ganciclovir, and the combination of G2-S16 or G2-S24P with ganciclovir increases the HCMV inhibition around 90 %. Conclusions Nanotechnology, in particular polyanionic carbosilane dendrimers, have proved their potential application against HCMV, being capable of inhibiting the infection by themselves or enhancing the activity of ganciclovir, the actual treatment. These compounds represent a low-cost approach to fight HCMV infections.